Application accuracy of the sleep decision tree to standardized patient cases by physiotherapists: An observational study. (18th November 2022) - Siengsukon, Catherine F.; He, Jianghua; Miller, Kenneth; Jewell, Dianne
ABSTRACT: Background: Physiotherapists assess lifestyle factors, including sleep health, that contribute to poor health outcomes. Recommendations of sleep screening assessments have been provided; however, physical therapists' ability to successfully identify which patients would benefit from additional consultation has not been established. Objective: To determine if physiotherapists can accurately apply an evidence-based sleep decision tree to four hypothetical standardized patient cases. Methods: Participants applied the sleep decision tree to the four standardized cases via an online platform. Likert scales were used to assess perception of ease of use, likelihood of use, and how helpful they thought the sleep decision tree would be. Descriptive analyses and multiple linear regression models were conducted. Results: Eighty-eight individuals participated in the study. Most participants correctly answered the cases with 1 and 3 decision points (92% and 84%, respectively). In contrast, few participants correctly answered the cases with 4 and 5 decision points (7% and 14%, respectively). Seventy-four (84%) respondents indicated the sleep decision tree was easy to use; 57 (65%) answered they were likely to use the sleep decision tree in clinical practice; and 66 (75%) said the sleep decision tree would be helpful to their clients. Conclusions: Physiotherapists were able to accurately apply a sleep decision tree to simpler patient cases but were frequently unable to apply it to more complex patient cases. This may be due to lack of education, perceived ease of using, and relevance of the sleep decision tree to their clinical practice. The sleep decision tree may aid physiotherapists in assessing sleep health, screening for sleep disturbances, and referring for further assessment.